The Effect of Frequencies Spraying of Forest Betel Leaf Extracts on Snails In Moringa Plants - Michael Daru Enggar Wiratmoko; Rusli Rustam; Hafiz Fauzana (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Moringa is a superior plant that has been widely developed in Indonesia. One of the obstacles found in the moringa nursery is the attack of snail pests (Achatina fulica Fer.). Pest control which is currently mostly carried out using synthetic chemical pesticides can have a negative impact on the environment. Therefore, an alternative pest control is needed, namely using vegetable pesticides from forest betel nut (Piper aduncum Linn.). This study aims to obtain the effective concentration of betel nut extract in controlling snails. The research was conducted at the Experimental Garden Technical Implementation Unit, Faculty of Agriculture, University of Riau. The research was conducted in January 2023 - May 2023. Testing the frequency of spraying forest betel leaf extract against snail pests, used a completely randomized design (CRD) with 4 treatments and 4 replications to obtain 16 experimental units. The treatment was without spraying forest betel extract, spraying intervals of forest betel extract 1 × 1 week, 1 × 2 weeks and 1 × 3 weeks. Based on the observations, spraying forest betel leaf extract once a week is the best frequency because it can cause 100% mortality with an initial death time of 18.75 hours after application, Lethal Time 50 191.25 hours after application, and an attack intensity of 4.35%.